LRAD – A Radiometer for the Lunar South Ppole Hopper µNOVA - Hamm, Maximilian; Grott, Matthias; Knollenberg, Jörg; Mueller, Nils; Robinson, M.; Atwell, M.; Martin, T. (2022)
The Lunar Prospector discovery of areas of neutron suppression and the subsequent interpretation of hydrogen enrichment near the lunar poles brought the possibility of volatile resources sequestered at the poles to the forefront of the lunar science community. Subsequently the LCROSS experiment showed that water ice is present within at least one permanently shadowed region (PSR) near the south pole and that it can be stable over geological timescales inside permanently shadowed regions (PSRs). Analysis of UV observations gathered by the Lunar Reconnaissance Orbiter Diviner instrument are consistent with the presence of surface frost in some PSRs with temperatures below 110 K. Further, the depth-to-diameter ratios of simple craters as determined from Lunar Orbiter Laser Altimeter (LOLA) altimetric measurements indicate that deposits of water ice in these cold traps may be up to 50 m thick. Moreover, water ice may be present in small PSRs at scales down to, and below 10 meters [5]. Such small-scale cold traps could significantly increase water inventory estimates and eventually simplify extraction.